Effects of long-term aspirin use on molecular alterations in precancerous gastric mucosa in patients with and without gastric cancer. Issue 1 (December 2017) - Michigami, Yuki; Watari, Jiro; Ito, Chiyomi; Hara, Ken; Yamasaki, Takahisa; Kondo, Takashi; Kono, Tomoaki; Tozawa, Katsuyuki; Tomita, Toshihiko; Oshima, Tadayuki; Fukui, Hirokazu; Morimoto, Takeshi; et al.
Abstract The risk of gastric cancer (GC) remains even afterH. pylori eradication; thus, other combination treatments, such as chemopreventive drugs, are needed. We evaluated the effects of aspirin on genetic/epigenetic alterations in precancerous conditions, i.e., atrophic mucosa (AM) and intestinal metaplasia (IM), in patients with chronic gastritis who had taken aspirin for more than 3 years. A total of 221 biopsy specimens from 74 patients, including atrophic gastritis (AG) cases without aspirin use (control), AG cases with aspirin use (AG group), and GC cases with aspirin use (GC group), were analyzed. Aspirin use was associated with a significant reduction ofCDH1 methylation in AM (OR: 0.15, 95% CI: 0.06–0.41, p = 0.0002), but was less effective in reversing the methylation that occurred in IM. Frequent hypermethylation including that ofCDH1 in AM increased in the GC group compared to the AG group, andCDH1 methylation was an independent predictive marker of GC (OR: 8.50, 95% CI: 2.64–25.33, p = 0.0003). In patients with long-term aspirin use, the changes of molecular events in AM but not IM may be an important factor in the reduction of cancer incidence. In addition, methylation of theCDH1 gene in AM may be a surrogate of GC.